Analysis of the Effect of Inflation and Total Population on the Open Unemployment Rate in East Java Province in 2013-2022 - Ricca, Dhinar; Mahardika, Titania; Eka, Tarisa (PT FORMOSA CENDEKIA GLOBAL, 2023)
East Java Province has a high open unemployment rate in Java during 2013-2022. The study aims to determine the effect of inflation and population on open unemployment in East Java Province in 2013-2022. This research is a research using descriptive quantitative method. Data were analyzed using the Ordinary Least Square (OLS) model. The results of the study show that inflation has no significant effect on open unemployment in East Java Province in 2013-2022, while the population has a significant effect on open unemployment in East Java Province in 2013-2022.